2002
DOI: 10.1046/j.0300-0664.2001.01456.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss increases circulating levels of ghrelin in human obesity

Abstract: This study provides evidence of a reversible suppression of ghrelin associated with obesity. The feasibility of measuring ghrelin in the circulation provides a new tool for the investigation of the complex hormonal regulation of appetite and energy balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
229
11
15

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(276 citation statements)
references
References 13 publications
21
229
11
15
Order By: Relevance
“…Studies based on intensive energy restriction (very low caloric diet) showed increasing ghrelin concentrations. 13,14 In contrast to this, our study with high-carbohydrate and low-fat diet demonstrated no significant increase in ghrelin levels despite a small but not significant tendency (increase in ghrelin levels of 4%). Probably the kind of treatment to reduce weight may have influenced the ghrelin levels and may explain the different study results.…”
Section: Ghrelin In Obese Children T Reinehr Et Alcontrasting
confidence: 99%
See 1 more Smart Citation
“…Studies based on intensive energy restriction (very low caloric diet) showed increasing ghrelin concentrations. 13,14 In contrast to this, our study with high-carbohydrate and low-fat diet demonstrated no significant increase in ghrelin levels despite a small but not significant tendency (increase in ghrelin levels of 4%). Probably the kind of treatment to reduce weight may have influenced the ghrelin levels and may explain the different study results.…”
Section: Ghrelin In Obese Children T Reinehr Et Alcontrasting
confidence: 99%
“…9 In obese adults and children, leptin levels have shown to be increased, while ghrelin levels are decreased. 7,[9][10][11] There are only few studies consisting of only a small number of subjects, which analyze the changes in ghrelin levels due to reduction of overweight in a time period of weeks up to months with contradictory results: four studies reported increasing ghrelin levels, [12][13][14][15] four studies no changes of ghrelin levels [16][17][18][19] and one study decreasing ghrelin levels after weight reduction. 20 Until now, there is only one study on ghrelin levels in obese children after weight reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin is a 28-amino-acid peptide hormone produced mainly in the stomach fundus and is the most potent appetitestimulating hormone coming from the gastrointestinal tract [29]. Ghrelin is generally up-regulated under conditions of negative energy balance and down-regulated in the setting of positive energy balance; fasting serum ghrelin levels are usually low in obese subjects compared with lean individuals [30], and fasting plasma levels rise with diet induced weight loss [14,31]. Ghrelin was shown to increase food intake dose-dependently in lean and obese Zucker rats [32].…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss has been shown to induce an increase in ghrelin levels. 62 Moreover, it has been shown that ghrelin may decrease BP, improve endothelial function and inhibit vascular oxidative stress in spontaneously hypertensive rats. 63 The endocannabinoids represent polyunsaturated fatty-acid derivatives, which take part in a large neuromodulatory signaling system for the control of balance between food intake and satiation.…”
Section: Mechanisms Of Obesity-induced Hypertension V Kotsis Et Almentioning
confidence: 99%